Speech input processing in children born with cleft palate: A systematic literature review with narrative synthesis. Issue 4 (14th June 2021) - Southby, Lucy; Harding, Sam; Phillips, Veronica; Wren, Yvonne; Joinson, Carol
Abstract: Background: Speech development requires intact and adequately functioning oral anatomy and cognitive 'speech processing' skills. There is evidence that speech input processing skills are associated with speech output problems in children not born with a cleft. Children born with cleft palate ± lip (CP±L) are at high risk of developing disordered speech output. Less is known about their speech input processing skills and whether they are associated with cleft‐related speech sound disorder (SSD). Aims: (1) To collate and evaluate studies reporting evidence regarding the speech input processing skills of children born with cleft palate in comparison with data from typically developing children or other comparison groups; and (2) to identify any available evidence regarding relationships between speech input processing skills and speech output in children born with CP±L. Methods & Procedures: Potentially relevant studies published up to November 2019 were identified from the following databases: Medline via Ovid, Embase via Ovid, Cinahl via Ebscohost, PsycInfo via Ebscohost, BNI via ProQuest, AMED via Ovid, Cochrane Library and Scopus. Inclusion criteria were: peer‐reviewed articles published in scientific journals, any design, published in English, participants born with a CP±L aged up to age 18 years who completed speech input processing assessments compared with normative data and/or a control or other comparison group. Critical Appraisal Skills Programme (CASP) checklists were used to quality appraise included studies. Outcomes & Results: Six studies were retained in the final review. There is some evidence that children born with CP±L perform less well than non‐cleft controls on some speech input processing tasks and that specific input processing skills may be related to errors in the children's speech. Heterogeneity in relation to study groups and assessments used, as well as small sample sizes, limits generalization of findings. Conclusion & Implications: There is limited evidence regarding the speech input processing skills of children born with CP±L. There are indications that children born with CP+/L may have difficulty in some aspects of speech input processing in comparison with children not born with a cleft, and that difficulties with some speech input processing tasks may be specific to errors in children's speech output. Further research is required to develop our understanding of these skills in this population and any associations with speech output. What this paper adds: What is already known on the subject: Few studies have been published that examine aspects of speech input processing in children born with CP±L. Theoretical models of speech processing, and published studies, propose that speech input processing skills are associated with SSD in children who were not born with a cleft. However, it is less clear whether there is any association between speech input processing and cleft‐related SSD. What this paper adds to existing knowledge: This review systematically collates and evaluates the published, peer‐reviewed evidence regarding speech input processing skills in children born with CP±L. The collated evidence indicates that some speech input processing skills differ between children with and without CP±L. There is some evidence, from a single study, that speech input processing of specific cleft speech characteristics (CSCs) may be associated with the presence of these CSCs in the speech output of some children born with CP±L. What are the potential or actual clinical implications of this work?: While the evidence is currently limited, increasing our knowledge of speech input processing skills in children born with CP±L contributes to our clinical understanding of the nature of cleft‐related SSD. The current evidence suggests that speech and language therapists should consider speech input processing skills when assessing children with cleft‐related SSD to support intervention planning. Considering these skills in relation to literacy development in these children may also be important.